The Stock Market Channel of Monetary Policy - Cosimano, Thomas; Chami, Ralph; Fullenkamp, Connel (Washington, D.C. : International Monetary Fund, 1999)
This paper argues that the stock market is an important channel of monetary policy. Monetary policy affects real economic activity because inflation levies a property tax on stocks in addition to an income tax on dividend payments. Inflation thus taxes stocks more heavily than it does bonds. Households alter their required rate of return as inflation changes, and firms adjust production in order to satisfy their shareholders' demands. As the stock market channel grows in importance, the appropriate intermediate target for the central bank is the price level, with price stability being the ultimate goal.
Off-Campus Access: No User ID or Password Required
On-Campus Access: No User ID or Password Required
Mode of access: Internet